Study of Working Conditions and Environmental Pollution, When Applying The Herbicide Zellec - A. K. Kurbanov; P. Kh. Khalikov; L. A. Shigakova; Sh. A. Islamova; Khusainova. Kn. Zh. (Scientific Trends, 2022)
In accordance with the tasks, studies were conducted to study occupational health and pollution of environmental objects when using Zellek. The drug was applied in the form of a liquid droplet aerosol. Field studies were conducted over two seasons of the drug. A hygienic assessment of working conditions when using the drug was carried out at the tractor driver’s workplace, swabs were taken from open areas of their skin integument, as well as overalls. Studies have been carried out to study the functional state of the organism of tractor drivers, tankers working with an herbicide. Studies of the study of working conditions with the use of Zellek showed that workers have a combined effect of chemical and physical factors. The process of applying Zellek is accompanied by its spread into the atmospheric air. In the air above the treated field 6 hours after use of the drug is not detected. The introduction of herbicides is accompanied by it getting into the soil and water of open reservoirs.
Keywords: Zellek, aerosol, intensity, temperature, environment, organism condition.